Efektivitas Terapi Akupresur Terhadap Intensitas Nyeri Persalinan Kala 1 Fase Aktif: Literature Review - Handayani, Ni Luh Widhi; Simanjuntak , Merida D (Maternal & Neonatal Health Journal, 2026)
Pregnancy is a period that begins from conception until the birth of the fetus. Pregnancy lasts for 9 months, or 40 weeks, or 280 days calculated from the first day of the last menstrual period (LMP). Many changes occur during pregnancy, one of which is physical changes that cause back pain. Management of pain in pregnant women can include non-pharmacological therapy, namely endorphin massage. This study aims to determine the effect of endorphin massage on reducing the intensity of back pain in pregnant women. Article search strategies were conducted through Google Scholar. The research method, using a literature review, refers to the issues, methodology, and consistency of the results obtained. Six articles met the criteria for review. Data were collected from articles in national journals from the period 2020–2025. The study results showed that there was a significant effect on reducing the intensity of back pain in pregnant women. Given the effect of endorphin massage on reducing back pain intensity, this endorphin massage therapy can be considered a safe, effective, and easily applied supportive intervention in the management of back pain in pregnant women in the third trimester.